Association of exopolysaccharide genes in biofilm developing antibiotic-resistant Pseudomonas aeruginosa from hospital wastewater. (7th December 2021) - Divyashree, M.; Mani, Madhu K.; Karunasagar, Indrani
Abstract: The study aimed to examine the relationship between antibiotic resistance, biofilm formation and genes responsible for biofilm formation. Sixty-six Pseudomonas aeruginosa isolates were obtained from hospital wastewater and analyzed for their antibiotic resistance. Biofilm production among the isolates was tested by indirect quantification method crystal violet assay. Biofilm-associated genes among these isolates psl, alg, and pel were also checked. The maximum resistance was observed for ampicillins (88.24%) followed by nalidixic (83.82%), and nitrofurantoin (64.71%), respectively. Biofilm phenotypes are distributed in the following categories: high 39.39% ( n = 26); moderate 57.57% ( n = 38), and weak 3.0% ( n = 2). Among the total isolates, biofilm-associated genes were detected in 84.84% ( n = 56) of isolates and the remaining isolates 15.15% ( n = 10) did not harbor any genes. In this study, pslB was the most predominant gene observed (71.21%, n = 47) followed by pslA (57.57%, n = 38), pelA (45.45%, n = 30), algD (43.93%, n = 29), and pelD (27.27%, n = 18), respectively. The present study reveals that the majority of the isolates are multidrug resistant being moderate and high biofilm formers. The study implies that biofilm acts as a machinery for bacteria to survive in the hospital effluent which is an antibiotic stress environment. HIGHLIGHTS: Hospital effluent carrying biofilm forming antibiotic resistant bacteria is a major threat to public health. Dissemination of these bacteria into the surrounding environment is of major concern. Bacterial biofilm formation enhances the antibiotic resistance. Infection caused by these multidrug resistant isolates are difficult to treat. Study emphasizes the need of appropriate wastewater treatment. Graphical Abstract